Assessment of body mass and its effect on blood pressure values according to nurses with a Bachelor of Nursing degree - Grabowska, Hanna; Narkiewicz, Krzysztof; Grabowski, Władysław; Grzegorczyk, Michał; Gaworska-Krzemińska, Aleksandra; Świetlik, Dariusz (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. The risk of developing high blood pressure is several times higher in obese people. Involving nursing staff in fighting obesity can play a vital role in the prevention of high blood pressure. Aim. To show the knowledge among a group of nurses with a Bachelor of Nursing degree about methods of assessing patient body mass, as well as the effect weight reduction has on blood pressure. Material and methods. This research is based on 116 qualified nurses (F-112, M-4; age 21-50; work experience 0-29 years). The research was carried out from June 2007 to January 2008 using diagnostic survey questionnaires. The research tool was our own questionnaire. Results. The results of the research show that 64.7% of those questioned have a knowledge about how to assess body mass using the BMI scale, while 89.7% correctly interpreted the results. 72.4% correctly gave the ideal waist size for women and men while only 18.1% had a knowledge of WHR. The effect of abdominal obesity on the development of high blood pressure was given by 95.7% of those questioned. However, just 32.8% correctly stated that a reduction in body mass has an effect on blood pressure values. The results of statistical analysis gave statistically significant differences of correct answers depending on work experience (p = 0.002), place of work p < 0.001) as well as position held (p < 0.001). There was no statistical significance depending on age, place where the person lives, family situation or type of post diploma education carried out by nurses with a Bachelor of Nursing degree. Conclusions. It is necessary to increase the knowledge among undergraduate students studying nursing of the methods of assessment of body mass and the importance of maintaining the correct body mass. It is also necessary to improve the effectiveness of pre and post graduate nursing education with regard to the knowledge of methods for assessing body mass in preventing high blood pressure and its consequences.